2016
DOI: 10.1007/s00787-016-0933-3
|View full text |Cite
|
Sign up to set email alerts
|

Stress hormones and posttraumatic stress symptoms following paediatric critical illness: an exploratory study

Abstract: In this exploratory case–control study, we investigated basal cortisol regulation in 5–16-year-old children, 3–6 months following PICU (paediatric intensive care) admission. This was nested within a study of child psychological and cognitive function; 47 children were assessed alongside 56 healthy controls. Saliva samples were collected three times per day (immediately after waking, waking +30 min, and waking +12 h) over two consecutive weekdays. In addition, data on posttraumatic stress symptoms were ascertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…There are indications that high evening cortisol levels are associated with PTSD symptoms in children following PICU admission 1. It is possible that use of exogenous corticosteroids may result in reduced PTSD symptom burden through a mechanism that also involves normalisation of the cortisol-mediated stress response in these children.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are indications that high evening cortisol levels are associated with PTSD symptoms in children following PICU admission 1. It is possible that use of exogenous corticosteroids may result in reduced PTSD symptom burden through a mechanism that also involves normalisation of the cortisol-mediated stress response in these children.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up assessments for PTSD symptoms and salivary cortisol were performed at 3–6 months post discharge. Primary results of this study have been reported elsewhere 1. For this secondary retrospective exploratory analysis, children under 8 years of age were excluded to conform to the validity of the PTSD scoring tool.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations